Peran Kepala Sekolah Dalam Mengembangkan Mutu Budaya Organisasi - ZM Abid Mohammady (Muslim Heritage, 2017)
Abstract: In the context of Indonesia, the quality of education seems to be something taboo to talk about, however, according to researchers the quality of education in Indonesia is very apprehensive. It is necessary for the role of headmaster and special efforts in developing a quality education institution through organizational culture as a value system that is understood, imbued, run jointly by members of the organization as a system of meaning or guidance for the organizers. This study aims to describe the three roles and impacts role of the headmaster role in developing the quality of organizational culture, they are: (1) the role of the headmaster as a manager; (2) the role of the headmaster as the educator; (3) the role of the headmaster as the supervisor; 4) The impact of the headmaster's role in developing the quality of organizational culture quality at SDMT Ponorogo. This research is categorized into a field research with qualitative descriptive approach and the research design was case study. The setting of study was at SDMT Ponorogo.  The findings showed that (1). The role of headmaster as manager encompasses conducting internal and external analysis, internalizing the Islamic value that is kemuhamadiyahan value. (2). The role of the headmaster as an educator includes involving educators in upgrading, workshops or training in order to provide opportunities for educators to improve their knowledge and skills by learning to the higher education, conducting cadre to members of organizational culture and creating jargon to motivate members of organizational culture. (3). The role of the headmaster as a supervisor comprises overseeing and Evaluating the performance and achievement of members of organizational culture, conducting weekly, monthly and semester meetings, monitoring achievements of educators and learners. (4) The impact of the school headmaster's role in developing the quality of organizational culture is organizational culture climate becomes harmonious and schools achieve more attainments.Abstrak: Dalam konteks Indonesia, mutu pendidikan seolah-olah menjadi barang yang tabu untuk diperbicangkan, dalam konteks tersebut kualitas pendidikan di Indonesia sangat memperihatinkan. Untuk itu diperlukan peran kepala sekolah dan Upaya khusus dalam mengembangkan sebuah mutu lembaga pendidikan melalui budaya organisasi sebagai sistem nilai yang dipahami, dijiwai, dijalankan secara bersama oleh anggota organisasi sebagai sistem makna atau pedoman bagi pelaku organisasi. Penelitian ini bertujuan untuk mendeskripsikan dan menjelaskan tiga peran serta dampak peran  kepala sekolah dalam mengembangkan mutu budaya organisasi, yaitu: (1) Peran kepala sekolah sebagai Manajer, (2) Peran kepala sekolah sebagai Educator, (3) Peran kepala sekolah sebagai supervisor, dan (4) Dampak peran kepala sekolah dalam mengembangkan mutu budaya organisasi di SDMT Ponorogo. Dengan menghasilkan temuan: (1).Peran kepala sekolah sebagai manajer diantaranya: melakukan analisis internal dan eksternal, menginternalisasi nilai keislaman yaitu nilai kemuhammadiahan. (2). Peran kepala sekolah sebagai educator diantaranya: mengikut sertakan pendidik dalam penataran, workshop atau pelatihan memberikan kesempatan kepada pendidik untuk meningkatkan pengetahuan dan keterampilannya dengan belajar ke jenjang pendidikan yang lebih tinggi, melakukan pengkaderan kepada anggota budaya organisasi. membuat jargon-jargon untuk memotivasi anggota budaya organisasi. (3). Peran kepala sekolah sebagai supervisor diantarnya: mengawasi dan mengevaluasi kinerja dan pencapaian anggota budaya organisasi, mengadakan rapat setiap, minggu, bulan dan semester, memantau prestasi pendidik dan peserta didik. (4) Dampak peran kepala sekolah dalam mengembangkan mutu budaya organisasi diantaranya: iklim budaya organisasi menjadi harmonis, sekolah menjadi lebih berprestasi.